Solve for L: S=2WL+2LH+2WH

Answers

Answer 1
Answer:

Answer:

Step-by-step explanation:

S = 2WL + 2LH + 2WH

S - 2WH = 2WL + 2LH

S - 2WH = L(2W + 2H)

(S - 2WH) / (2W + 2H) = L <===


Related Questions

Find tan A for the triangle below. a. 2.5 b. 0.4 c. 2.67 d. 0.375
11. Pam's patio IS shown below V What are me perimeter and area of the patio 1 . r Could a square with whole number side lengths have the same perimeter as the patio The same area Explain (14-8)
Was is 439 over 937 in simplest form
Which point represents the order pair (2,-4)
At Funland, all rides cost $1. Angela has $21.50. How many rides can she take?

Evaluate z + z + z for x = 2, y = -3, z = -4.

Answers


" z + z + z " is just  3z  and doesn't depend on 'x' or 'y'.

If  z=-4, then (z + z + z) = 3z = -12.

Who knows the answer

Answers

Answer:

the value of X is -13.

Step-by-step explanation:

Identify the property shown: (5^3)^2 = 5^3 • ^2

A) Power of a Power Property
B) Quotient of Powers Property
C) Product of Powers Property
D) Power of a Product Property

Answers

Since (a^m)^n=a^mn, you multiply the exponents and you get their product, which will be the new exponent of the base.Therefore, the answer would be C. Product power of a Product Property.

Multipli lui 6 cuprinsi intre 11 si 39 sunt

Answers

Multiples of 6 between 11 and 39 are

Answer:

12, 18, 24, 30, 36

Step-by-step explanation:

Given.

Number of multiple is 6

Lower limit is 11.

and upper limit is 39.

So, after 11

12 is multiple of 6

18 is multiple of 6

24 is multiple of 6

30 is multiple of 6

36 is multiple of 6

Therefore, total five number is multiples of 6 between 11 and 39

(12, 18, 24, 30, 36)

plz I need this help 30 points What is the approximate percent decrease when a fish count goes down from 850 to 500?

Answers

Increase=New number - Original number 
Increase=500-850=-350 
%increase=Increase/original number X 100 
%increase= -350/850 X 100 = -41.18% 

Number is negative because it is a percentage decrease. 


What is x+y+4x-3x+2y+ 3y

Answers

4x+x+y-3x+2y+3y
=2x+6y
x+y+4x-3x+2y+ 3y=x+x+y+5y=2x+6y